Cost Assessment Modelling of Treatments for Highly Active Relapsing Multiple Sclerosis - Petri Mankinen; Tuomas Lundström; Erkki Soini; Marja-Liisa Sumelahti; Juhani Ruutiainen; Ulla Niskala; Elina Järvinen (SPRINGER, 2022)
Introduction Cost assessment modelling (CAM) of treatments in highly active relapsing multiple sclerosis was conducted. Methods The CAM was developed using the R programming language. The PICOSTEPS health technology assessment framework was applied in the CAM. Modelled patients were 280 adults with highly active relapsing multiple sclerosis eligible for disease-modifying treatment. Intervention was cladribine tablets, a new and reimbursed oral treatment for highly active relapsing multiple sclerosis in Finland. Comparators included fingolimod, the most used oral reimbursed treatment for the highly active disease, and natalizumab, the most used intravenous treatment, and a treatment mix (80% use fingolimod, 20% use natalizumab) in Finland. Outcomes presented expected annual and cumulative drug-associated costs in the overall population and per patient. Setting was modelled public specialist care in Finland. Time was set to 4 years, without discounting. Effects covered expected drug-associated costs (screening, acquisition, administration, monitoring, adverse events, travelling, productivity). Perspective was a limited societal perspective. Sensitivity analyses regarding all PICOSTEPS components were conducted. Results Cladribine tablets were projected to be cost saving in comparison to fingolimod, natalizumab and treatment mix. The respective modelled savings were euro4,598,742, euro16,249,701 and euro6,928,934 in the overall population, and euro16,424, euro58,035 and euro24,746 per patient, respectively, during the 4 years. The most important cost driver was drug costs, representing 96.3%, 96.0% and 83.4% of modelled costs associated with cladribine tablets, fingolimod and natalizumab, respectively. Cladribine tablets sustained their affordability in the sensitivity analyses. From the perspective of health care payer, cladribine tablets' savings were projected to be euro4,514,509, euro15,145,366 and euro6,640,680 in the overall population, and euro16,123, euro54,091 and euro23,717 per patient in comparison to fingolimod, natalizumab and treatment mix, respectively. Conclusion Based on the CAM, cladribine tablets were projected to robustly save modelled drug-associated costs in comparison to fingolimod, natalizumab and their mix in Finland.